Islamic Financial Inclusion Determines Strategic Agility Diversification Investment to Improve the Financial Performance of BMT in Central Java - Setyo Budi Hartono; Yuyun Ristianawati (KEUNIS, 2026)
In Indonesia, the efforts of BMT to improve its financial performance are hindered by Islamic Financial Inclusion (IFI), whose main provision—namely collateral—can prevent customers from applying for financing. Therefore, managers must adopt a novel non-financial approach, namely Strategic Agility Diversification Investment (SADI), which is developed through measurements of investment alignment, risk innovation, and data growth using the Markowitz theory and physical aptitude. This study tests the SADI indicators on 116 BMT managers in Central Java using AMOs 20.0. The results reveal that the variables of IFI—i.e., FI challenges, benefits, and realization—influence how SADI improves BMT’s financial performance. Furthermore, the direct effect of IFI on BMT’s financial performance is also tested, and the result shows a negative relationship. Thus, it can be concluded that the intervention of SADI in non-financial aspects is highly decisive in achieving IFI for BMT’s financial performance enhancement.